Genipin as a Cross-linker in a Ciprofloxacin Delivery System Containing a Bovine Hydroxyapatite-Collagen Composite for Bone Infections - Nurul Fitriani; Aniek Setiya Budiatin; Esti Hendradi (Journal of Tropical Pharmacy and Chemistry, 2023)
The purpose of this research was to design an implant for a ciprofloxacin-based drug delivery system by combining bovine hydroxyapatite and collagen with genipin as the crosslinking agent. The production of ciprofloxacin implants using bovine hydroxyapatite:collagen blend (70:30). In addition, this synthetic preparation was made using three various concentrations of genipin (0.6, 0.8, and 1.0%). The pellets were created by compressing the implants. The tablets are cylindrical with a diameter of 4.0 mm and a weight of 100.0 mg. Ciprofloxacin cultures were characterized for swelling rate, porosity, density, compressive strength, morphology (SEM), dose, and drug release in vitro. The addition of genipin as a crosslinking agent may maintain ciprofloxacin release consistent with in vitro therapeutic levels of ciprofloxacin. These results are supported by compressive strength data, where the addition of genipin concentrations induces higher implant stiffness and scanning electron microscopy photomicrographs reveal small pore sizes and BHA adhere to collagen fibers so that ciprofloxacin is completely dispersed in the implant after cross-linking with genipin. As a drug delivery system for osteomyelitis, it can be concluded that the use of genipin as a cross-linking agent can sustain ciprofloxacin release commensurate with in vitro therapeutic levels of ciprofloxacin for 30 days.